Influence of gas packing and orientation on FTIR activity for CO chemisorption to the Cu paddlewheel. Issue 40 (23rd September 2015) - Wang, Cheng-Yu; Ray, Paramita; Gong, Qihan; Zhao, Yonggang; Li, Jing; Lueking, Angela D.
Abstract : In situ Fourier-transform infrared (FTIR) spectroscopy is able to probe structural defects via site-specific adsorption of CO to the Cu-BTC (BTC = 1, 3, 5-benzenetricarboxylate) metal–organic framework (MOF). Abstract : In situ Fourier-transform infrared (FTIR) spectroscopy is able to probe structural defects via site-specific adsorption of CO to the Cu-BTC (BTC = 1, 3, 5-benzenetricarboxylate) metal–organic framework (MOF). The temperature-programmed desorption (TPD) of CO chemisorbed to Cu-TDPAT (TDPAT = 2, 4, 6-tris(3, 5-dicarboxylphenylamino)-1, 3, 5-triazine) is virtually identical to Cu-BTC, suggesting CO chemisorbs to the open metal site at the axial position of the copper paddlewheel that is the building unit of both MOFs. Yet, despite an increased gravimetric CO : Cu ratio, CO chemisorbed to Cu-TDPAT is FTIR inactive. We rule out the presence of residual solvent, thermal degradation, adsorption temperature, and ligand-induced electronic effects at the adsorption site. TPD at increased pressure suggests the multiple CO per Cu site rearrange in Cu-TDPAT as a dynamic function of temperature and pressure. Thus, the FTIR inactivity of CO chemisorbed to Cu-TDPAT is attributed to orientation and/or packing of the CO relative to the Cu binding site. The results suggest dynamic chemisorption complicate extension of a site-specific in situ FTIR probe of gas adsorption. For both Cu-BTC and Cu-TDPAT, the in situ FTIR probe is a less sensitive probe of defects than X-ray photoelectron spectroscopy and nitrogen adsorption.